Synthesis and cytocompatibility of manganese (II) and iron (III) substituted hydroxyapatite nanoparticles - Li, Yan (2013)
Manganese (II) and iron (III) substituted hydroxyapatite (HA, Ca10(PO4)6(OH)2) nanoparticles were synthesized using wet chemical method. All samples were single-phase, non-stoichiometric and B-type carbonated hydroxyapatite. Compared with pure HA, Mn2+ substituted (MnHA) and Fe3+ doped HA (FeHA) did not demonstrate significant structure deviation. Since ion exchange mechanism was applied for the synthesis process, the morphology and particle size were not significantly affected: all samples were elongated spheroids of around 70 nm. The presence of Fe and Mn was confirmed by energy dispersive X-ray spectroscopy (EDX) while the concentrations were quantified by inductively coupled plasma (ICP). Fe3+ ions were more active than Mn2+ ions in replacing Ca2+ ions in HA lattice structure. The magnetic property of HA was modified by substitution with Fe. The Fe5 (Feadded/Caadded = 5% by molar ratio) was paramagnetic while pure HA was diamagnetic. Results of extraction assay from cells cultured in extracted medium for 72 h suggested that both MnHA and FeHA were non-cytotoxic to osteoblast cells. Meanwhile, the presence of Fe3+ ions in HA demonstrated significant positive effect on osteoblast cells, where the cell number on Fe5 pellets was twice that of pure HA and MnHA samples.